Islamic Movements Face an Emerging Threat and Tunisian Political Environment: Presidential Coup, Democracy, and Aristocracy - Muhammad Asad Latif (Penerbit Hellow Pustaka, 2024)
In 2011, the popular revolt brought about change in the Tunisian presidential palace as it transitioned from authoritarianism to a condition of liminality. However, following the Tunisian President's proclamation, only the democratic success story of the Arab Spring is under jeopardy after ten years of democratic transition. This article seeks to show how the President has increased his authority by invoking Article 80 of the Constitution. It also explains how this action violates the constitution and has a detrimental effect on the political environment. As a result, Tunisia's Islamic movement has dominated the political landscape of the nation since the 2011 uprising and is seen as the leader of the Islamic identity and democratic movement. Finally, it comes to a conclusion that a coup from the Tunisian president occurred amid Rashid Al-Ghannouchi, the Movement's founder and speaker of the Parliament, showing leniency toward Islamic doctrine. Although it appears that the situation is still precarious, Al-Nahda leadership is once again playing a crucial role in fostering a stable political environment through discussion. The main and secondary data in this article have been evaluated using the Discourse Analysis method and its Critical Discourse Analysis method.